Новый для науки вид слизня рода Deroceras (Gastropoda, Limacidae) из Крыма - Скляр, И.Я. (Вестник зоологии, 1975)
In the forest zone of the Crimean Peninsula representatives of the new for science species Deroceras ramosum sp. n. were found. This species differs from the described earlier species of the genus Deroceras in peculiarities of the penis structure.